A PROTOYPE OF DIGITAL BLOOD PRESSURE MEASUREMENT DEVICE BASED ON ARDUINO UNO AND MOBILE APPLICATION - Maarif, Muhammad Rifqi; Priyanto, Agung (Compiler, 2018)
Blood pressure is one of the vital sign which widely used as a parameter for medical examination. In some cases likes hypertension, cardiovascular disease or routine examination of pregnant woman, blood pressure test which performed frequently become an important thing. Based on those cases, hence an availability of blood pressure measurement devices will become significant. Thus, in this research, we developed a prototype od digital blood pressure measurement device by using Arduino Uno microcontroller and Android based mobile application. In general, Arduino Uno was equipped with pressure sensorMPX5050DP, those devices will be used for blood pressure measurement. Then the result will be sent and displayed to mobile application. Data transmission between hardware and mobile application was done by using bluetooth module